The Environment as an Unrecognized Reservoir for Community-Associated Methicillin Resistant Staphylococcus aureus USA300: A Case-Control Study - Uhlemann, Anne-Catrin (Public Library of Science, 2011)
BACKGROUND: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections are spreading, but the source of infections in non-epidemic settings remains poorly defined. METHODS: We carried out a community-based, case-control study investigating socio-demographic risk factors and infectious reservoirs associated with MRSA infections. Case patients presented with CA-MRSA infections to a New York hospital. Age-matched controls without infections were randomly selected from the hospital's Dental Clinic patient population. During a home visit, case and control subjects completed a questionnaire, nasal swabs were collected from index respondents and household members and standardized environmental surfaces were swabbed. Genotyping was performed on S. aureus isolates. RESULTS: We enrolled 95 case and 95 control subjects. Cases more frequently reported diabetes mellitus and a higher number of skin infections among household members. Among case households, 53 (56%) were environmentally contaminated with S. aureus, compared to 36 (38%) control households (p = .02). MRSA was detected on fomites in 30 (32%) case households and 5 (5%; p<.001) control households. More case patients, 20 (21%) were nasally colonized with MRSA than were control indexes, 2 (2%; p<.001). In a subgroup analysis, the clinical isolate (predominantly USA300), was more commonly detected on environmental surfaces in case households with recurrent MRSA infections (16/36, 44%) than those without (14/58, 24%, p = .04). CONCLUSIONS: The higher frequency of environmental contamination of case households with S. aureus in general and MRSA in particular implicates this as a potential reservoir for recolonization and increased risk of infection. Environmental colonization may contribute to the community spread of epidemic strains such as USA300.